The relationship of transformational leadership on project management in multinational companies in Malaysia - Kiran, Alina (2025)
This study investigated the relationship between transformational leadership (TFL) and project management (PM) in multinational companies (MNCs) in Malaysia, focusing on the mediating roles of project management assets (PMA) and psychological empowerment (PE). TFL, recognized for its capacity to inspire and drive change, was examined in the context of PM by evaluating its impact on key performance indicators such as timeliness, costeffectiveness, and stakeholder satisfaction. Utilizing the Value, Rarity, Imitability, and Organizational Support (VRIO) framework within the Resource-Based View (RBV) paradigm, this research explored the significance of PMA in achieving a competitive advantage throughout the PM process. A quantitative analysis was conducted on data collected from 60 Malaysian MNCs using Partial Least Squares Structural Equation Modelling (PLS-SEM) to assess the correlations among TFL, PMA, and project efficiency. The findings revealed that TFL positively influenced project outcomes, including timeliness, cost-effectiveness, and stakeholder satisfaction. PMA and PE acted as significant mediators, with robust project management resources and empowered employees leading to improved project performance and competitive advantage. Furthermore, several contextual factors specific to the Malaysian business environment were identified as moderators in the proposed relationships, highlighting the need for cultural sensitivity and adaptability in leadership practices. The study concluded that TFL is crucial for project success in Malaysian MNCs, and its effectiveness is enhanced by strong project management assets and an empowered workforce. These insights contribute significantly to the literature on leadership and project management by offering practical recommendations for leaders, project managers, and policymakers in developing effective strategies to enhance PM in Malaysia’s dynamic and culturally diverse business climate. Ultimately, this study adds valuable knowledge applicable globally and specifically within the Malaysian context, enriching ongoing discussions in the fields of leadership and project management research